Banks, oligopolistic competition, and the business cycle: A new financial accelerator approach - Alexander Totzek (Kiel University, Department of Economics, 2011)
In the last two decades a body of literature highlights the role of financial frictions for explaining the development of key macroeconomic variables. Moreover, the financial crisis 2007-2009 again sheds light on the importance of this topic. In this paper, we contribute to the literature by simultaneously explaining two empirical observations. First, mark-ups on the loan market react counter-cyclical. Second, the number of banks operating in the economy significantly co-moves with GDP. Therefore, we develop a DSGE model which incorporates an oligopolistic banking sector with endogenous bank entry. The resulting model generates significant accelerating effects which are even larger than those obtained in the famous financial accelerator model of Bernanke et al. [Bernanke, B., Gertler, M., Gilchrist, S., 1999. The financial accelerator in a quantitative business cycle framework. In: Handbook of Macroeconomics. North-Holland, Amsterdam] and performs remarkable well when comparing the generated second moments of real and financial variables with those observed in the data.
Keywords: E44; E32; 330; Oligopolistic competition; Bank entry; Financial accelerator